Photodynamic therapy and nanomedicine: current knowledge, limitations, and applications in oral squamous cell carcinoma: a narrative review - Fariba Esperouz; Mauro Lorusso; Andrea Santarelli; Alfredo De Lillo; Lorenzo Lo Muzio; Domenico Ciavarella; Lucio Lo Russo (Frontiers in Oncology)
Oral squamous cell carcinoma is still a global health issue, even if oral cavity is an easily accessible anatomical site, the diagnosis is still delayed. Conventional treatments, like chemotherapy and radiotherapy, are usually employed, but not without complications. These drawbacks have necessitated the need for new therapies, one of these is photodynamic therapy (PDT). Nanotechnologies-enhanced PDT has significantly improved tumor targeting, bioavailability, and light absorption, paving the way for its application in early-stage of oral squamous cell carcinoma (OSCC) and as part of combination therapies for advanced cases. Despite the potential advantages of PDT, such as tumor selectivity, minimization of systemic side effects and repeatability of treatment, some limitations still restrict its clinical application. Despite these challenges, its application in oral squamous cell carcinoma and oral potentially malignant disease is promising, both alone or in combination with other therapies. Addressing such pros and cons of this technique, PDT may then be a possible adjuvant tool in the management of OSCC.